Discovery of another new species of Charadrahyla (Anura, Hylidae) from the cloud forest of northern Oaxaca, México - Canseco-Márquez, Luis; Ramírez-González, Cynthia Grisell; González-Bernal, Edna (Zootaxa, 2017)
Charadrahyla esperancensis, a new species of tree frog, is described from the cloud forest of Sierra d Juárez on the northern slopes of Oaxaca. This species is sympatric with C. nephila and is distinguished by the presence of a protuding snout with a distinctive downward slope posterior to the nostril in lateral view, with an evident rostral keel, and the flanks and anterior and posterior surfaces of limbs with yellow spots. With the discovery of this new species, the species number of the genus increases to seven and adds another species of Charadrahyla for the assemblage of anurans from northern Oaxaca. This is the first instance of sympatry of species in the genus Charadrahyla. Additionally, we provide a key to the species of the genus.